1990
DOI: 10.1007/bf00857656
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of certain factors in the haemolytic-uraemic syndrome

Abstract: The prognostic significance of certain factors in the outcome of the haemolytic-uraemic syndrome (HUS) was evaluated. Seventy-three children with HUS were observed; 35 recovered without residual abnormalities, 6 had normal renal function with hypertension (HT) and/or urinary abnormalities, 5 had chronic renal failure, 1 child required chronic dialysis treatment, 4 children died of end-stage renal failure, and 22 died of acute renal failure (ARF). To identify the risk factors which influence prognosis, a logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

1991
1991
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
2
5
2
Order By: Relevance
“…In our study the proportion of HUS patients developing CRF was higher when the disease had an atypical com pared to a typical (postenteropathic) onset. This finding is in accordance with the experience from other centers [15,[22][23]. Age was not a significant predictor of outcome in our study; however the youngest children (< 1 year) pre sented the lowest recovery rate, possibly related to their high incidence of severe CNS involvement.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In our study the proportion of HUS patients developing CRF was higher when the disease had an atypical com pared to a typical (postenteropathic) onset. This finding is in accordance with the experience from other centers [15,[22][23]. Age was not a significant predictor of outcome in our study; however the youngest children (< 1 year) pre sented the lowest recovery rate, possibly related to their high incidence of severe CNS involvement.…”
Section: Discussionsupporting
confidence: 81%
“…Severe arterial hypertension in the acute phase of HUS may also have a prognostic significance as reported earlier [22]. We could further confirm that patients with a predomi nant arterial involvement in renal tissue are associated with a worse prognosis compared to those with isolated glome rular changes [10], In contrast to other investigators [19] we observed no relationship between the outcome and the total leukocyte count.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Most recent series report an acute mortality rate of between 3% and 16% [3 -9], although in other series it has been as high as 30% [15]. This may reflect different management as well as variability in the severity of the disease.…”
Section: Discussionmentioning
confidence: 91%
“…However, an analysis of their data reveals that after 15,23 and 24 days of oligu ria, respectively, follow-up GFR was reduced in each of the 3 patients and that proteinuria was present in 2 of the patients. Sieniawska et al [16] reported that the duration of anuria was not a statistically significant prognostic fac tor. In their study, all 73 children were anuric, and 36% of these children died.…”
Section: Oliguria or Anuria Are Reported To Occur In 41-100% Of Childmentioning
confidence: 99%